The Jews of Pinsk, 1881 to 1941 - Shoḥeṭ, ʻAzriʼel (Stanford studies in Jewish history and culture., 2012)
This title provides a detailed and comprehensive history of the Jewish community in Pinsk. The second portion of this study focuses on Pinsk's turbulent final 60 years, showing the reality of life in this important, and in many ways representative Eastern European Jewish community.